Réponses

2013-12-06T06:26:30+01:00
F (x)=x+xau carre    l'image de la fonction f du nombre   a ) -2    b)  -3   c ) -1

a) f(-2) = -2 + (-2)^2 = -2 + 4 = 2
b) f(-3) = -3 + (-3)^2 = -3 + 9 = 6
c) f(-1) = -1 + (-1)^2 = -1 + 1 = 0
Meilleure réponse !
2013-12-06T07:47:23+01:00
F (x) = x + x²

f (-2) = -2 + (-2)²     f (-3) = -3 + (-3)²     f (-1) = -1 + (-1)²
f (-2) = -2 - 2²         f (-3) = -3 -3²          f (-1) = -1 - 1²
f (-2) = -2 + 4         f (-3) = -3 + 9         f (-1) = -1 +1
f (-2) = 2                f (-3) = 6               f (-1) = 0